An Analysis of Idiom Translation Strategies in The Life of Pi By Yaan Martel - Ongkosaputri, Bella Pratama (Universitas Muhammadiyah Lampung, 2025)
Idiom is a fixed group of words which has a particular meaning. Translating idioms to another language can be complicated and quite challenging because idioms cannot be translated word-by-word. This research aims to identify English idioms in Yaan Martel’s Life of Pi and to examine the translation strategies used by Tanti Lesmana in translating the novel into Indonesian based on Mona Baker’s (1992) theory. The data of this qualitative research were collected from Life of Pi as the Source Text (ST) and Kisah Pi as the Target Text (TT). The results show that there are 18 idioms found in the novel. The data of ST idioms were verified by checking their existence in online dictionaries. To determine their translation strategies, the researchers analyzed the meaning of the ST idioms then found their equivalences in Kamus Ungkapan Bahasa Indonesia (Badudu, 2008). These idioms were translated using three out of four translation strategies. The most frequently applied strategy is translation by paraphrase with 13 idioms, translation by using an idiom of similar meaning and dissimilar form of 4 idioms, and finally translation by omission of 1 idiom. Translation by paraphrase is the most frequently applied strategy because of the difficulty in finding equal idioms in target text.